(untitled) (REVISTA NODO, 2017)
The complexity of phenomena and the variety of relationships that involve sustainability, such as the survival of millions of living species on the planet (as well as the disappearance of many others) and their relationship with the ecosystems of nature and of these with Society, as an Economist, has led me to ask myself: what is the new role of the economy within society? Wis question has motivated me to study and write some initial lines that I want to refine, until reaching a greater depth in the subject to present my opinions to the consideration of the readers, until achieving the dynamics of the discussion that deserves the passion between the academic, the cognitive and the sensory in the life we lead.